Analysing science teachers’ difficulties in teaching the concept of electricity in junior high school - Hermawati, Tina (Research in Physics Education, 2022)
Electricity is a material that is considered difficult for science teachers to provide understanding to students so as to encourage researchers to find out what are the obstacles for science teachers in teaching the concept of electricity in junior high schools. The focus of this research is trying to uncover what obstacles are experienced by science teachers in teaching electricity in terms of facilities and infrastructure, preparation of lesson plans, learning processes, and assessment of learning outcomes. This study uses a case study research design with quantitative and qualitative approaches with the subject being a science teacher who is a member of the science teacher community in Garut Regency. Based on the results of the study, it can be concluded that: (1) teachers experience obstacles in terms of facilities because of inadequate teaching aids and also the absence of laboratory personnel so that activities in the laboratory are limited, (2) teachers also experience obstacles in terms of lesson planning, the obstacles experienced are the teachers are not yet creative in developing learning media for dynamic electricity, there is also no development of modules and worksheets, (3) in the implementation of electricity learning the teacher has difficulty in delivering electricity material related to equations/formulas because the teacher’s understanding of dynamic electric formulas is limited and students’ mathematical abilities are low, (4) in the assessment and evaluation of learning teachers experience obstacles in developing affective and psychomotor assessments, the ability of teachers to develop tests is low, and the use of various forms of assessment instruments.